2021
DOI: 10.1002/advs.202101793
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Triboelectric and Flexoelectric Charge Transfer at the Nanoscale

Abstract: The triboelectric effect is a ubiquitous phenomenon in which the surfaces of two materials are easily charged during the contact-separation process. Despite the widespread consequences and applications, the charging mechanisms are not sufficiently understood. Here, the authors report that, in the presence of a strain gradient, the charge transfer is a result of competition between flexoelectricity and triboelectricity, which could enhance charge transfer during triboelectric measurements when the charge transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…[ 58 ] As a result of mixed triboelectric and flexoelectric charge transfer at the interface between the rough coating and the slots, we can observe that charge transfer is reversed with material strain, when both effects are in opposite directions. [ 59 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 58 ] As a result of mixed triboelectric and flexoelectric charge transfer at the interface between the rough coating and the slots, we can observe that charge transfer is reversed with material strain, when both effects are in opposite directions. [ 59 ]…”
Section: Resultsmentioning
confidence: 99%
“…32 Also, Qiao et al presented that both the amount and direction of charge transfer can be modulated by manipulating the mixed triboelectric and flexoelectric effects. 33 As mentioned earlier, the mechanism analysis and implementation of flexoelectric effect-based devices have been demonstrated along with the synergistic outcome of hybridization with the piezoelectric or triboelectric effects. However, the effective implementation, practical applications, and systematic mechanistic analysis of self-powered mechanical sensors based on the flexoelectric effect have not been comprehensively examined.…”
Section: Introductionmentioning
confidence: 93%
“…For instance, Kim et al reported flexoelectric-boosted electromechanical properties of piezoelectric nanoparticles using an induced built-in strain gradient in a heterogeneous core–sphere nanostructure of BaTiO 3 @SrTiO 3 . Also, Qiao et al presented that both the amount and direction of charge transfer can be modulated by manipulating the mixed triboelectric and flexoelectric effects . As mentioned earlier, the mechanism analysis and implementation of flexoelectric effect-based devices have been demonstrated along with the synergistic outcome of hybridization with the piezoelectric or triboelectric effects.…”
Section: Introductionmentioning
confidence: 95%
“…The emerging triboelectric nanogenerator (TENG) is an indispensable way to convert mechanical energy into electrical energy, [ 9 , 10 , 11 , 12 ] successfully harvests diverse kinds of mechanical energy, [ 13 , 14 , 15 ] including wind energy, [ 16 , 17 , 18 ] water wave energy, [ 19 , 20 , 21 , 22 , 23 , 24 ] sound energy, [ 25 , 26 ] and human movement, [ 27 , 28 , 29 ] and has shown its value in marine‐related fields such as ship anti‐corrosion, water purification, and early warning. [ 6 , 30 , 31 ] Over the past few years, with the hard work of more than 50 research groups worldwide, [ 32 , 33 , 34 ] TENG has made rapid advances in output performance [ 17 , 35 , 36 , 37 , 38 ] and device architecture for blue energy harvesting.…”
Section: Introductionmentioning
confidence: 99%